Gender and Fashion Style Choices in University Students - Rahma, Inke Miladunka; Herawati, Erna (Jurnal Sosiologi Pendidikan Humanis, 2024)
This article discusses the connection between gender and fashion style choices among university students. It highlights the role of socialization, enculturation, and internalization in shaping students' understanding of gender and their fashion preferences. Through a qualitative phenomenological approach, the study explores the experiences of gender socialization among students and examines the relationship between gender and fashion choices. The findings indicate that there is no direct link between gender and students' fashion style preferences. However, fashion is viewed as a medium for expressing one's gender identity. The study finds that students exhibit flexibility in their fashion choices, adapting them to social contexts, specific events, and personal comfort. Nevertheless, the influence of gender socialization, enculturation, and internalization acquired since childhood is evident in their fashion decisions. Overall, the research emphasizes the complexity and individuality of students' fashion style choices within the broader context of gender. Gender dan Pilihan Style Fashion pada Mahasiswa Artikel ini melihat bahwa konsep gender yang berlaku pada setiap mahasiswa didapatkan melalui sosialisasi, enkulturasi, internalisasi dari agen sosialisasi yang berbeda-beda. Selain itu, penelitian ini juga mengulas lebih dalam kaitan konsep gender dengan pilihan style fashion pada kelompok sosial yang khusus, yaitu mahasiswa. Penelitian ini menggunakan pendekatan kualitatif-fenomenologi untuk menelusuri dan menggali pengalaman sosialisasi, internalisasi, dan enkulturasi gender para mahasiswa, dan kaitan antara hal itu dengan pilihan style fashion mereka. Hasil penelitian ini menemukan bahwa terdapat/tidak terdapat kaitan antara gender dan pilihan style fashion mahasiswa. Dalam hasil penelitian ini melihat fashion sebagai salah satu media dalam mengekspresikan identitas gender. Meskipun mahasiswa menunjukkan fleksibilitas dalam pilihan fashion dengan menyesuaikan dengan konteks sosial, acara tertentu, dan kenyamanan pribadi dengan berusaha untuk menerapkan sosialisasi, enkulturasi, dan internalisasi gender yang didapatkan sejak kecil.